استحداث مقاطعات ادارية في الجزائر في ظل انتهاج سياسة تقشفية خطوة مناسبة في الوقت غير المناسب - لعبيدي, الأزهر (unuversity of eloued- جامعة الوادي, 2017)
تتناول هذه الدراسة التقسيم الاداري الجديد في الجزائر الذي نص عليه المرسوم الرئاسي رقم 140-15 المؤرخ في 27 ماي 2015 المتضمن إحداث مقاطعات إدارية داخل بعض الولايات وتحديد القواعد الخاصة المرتبطة بها، حيث تم من خلاله استحداث عشر مقاطعات ادارية جديدة في منطقة الجنوب كمرحلة أولى، على أن يتم استحداث مقاطعات ادارية أخرى في مناطق الهضاب العليا في مرحلة لاحقة. وتركز هذه الدراسة عن الجدوى من استحداث تلك المقاطعات الجديدة بصلاحيات محصورة جدا مع مضاعفة حجم الإنفاق العمومي، وكذا امكانية الموازنة بين فكرة إعادة التنظيم الاداري الجديد والصعوبات المالية التي تعيشها البلاد.This study deals with the new administrative division in Algeria as stipulated in the presidential Decree No. 140-15 of 27 May 2015, which includes the establishment of administrative districts within some states and the establishment of special rules related to them. Ten new administrative districts were established in the South as a first stage, With the introduction of other administrative districts in the higher plateaus as a second stage. The study focuses on the feasibility of introducing these new provinces with very limited powers with doubling the volume of public expenditure, as well as the possibility of balancing the idea of the new administrative reorganization with the financial difficulties the country suffers from.
مقال
Keywords: التقسيم الاداري-المقاطعات الاداريالصعوبات المالية-الانفاق العمومي; Administrative division, districts administrative, the financial difficulties, public expenditure.